Alkenone and TEX86 data for MIS 6 to 5 on the Brazilian Margin - Bahr, André; Jaeschke, Andrea; Hou, Alicia Meng Xiao; Meier, Karl J F; Chiessi, Cristiano Mazur; Albuquerque, Ana Luiza Spadano; Friedrich, Oliver (PANGAEA, 2023)
We generated alkenone- and TEX86- based paleotemperature estimates for MIS 6-5 in core M125-55-7 (offshore Eastern Brazil) to text whether previously generated foraminiferal Mg/Ca SST are seasonaly biased. We find that alkenone and Mg/Ca-temperatures reflect annual mean SST with a transient winter bias of alkenone SST during MIS 5a-c. The winter-bias might relate to increased upwelling activity as indicated by higher abundances of G. bulloides. TEX86 temperatures (despite showing annual mean SST in core tops) deviate by up to 6°C to lower temperatures which we attribute to increased input of terrestrial GDGT during MIS 6 as indicated by an high BIT index and (ii) migration of the TEX86 producers to deeper levels within the water column following changes in vertical particle flux efficiency.
Keywords: Alkenone; BIT index; foraminifera abundance; TEX86